Interaction between the components in Tm-Cr-Ge system at 1070 K - Romaka, L.; Stadnyk, Yu.; Romaka, V.V.; Konyk, M. (Physics and Chemistry of Solid State, 2022)
The phase equilibrium diagram of the Tm–Cr–Ge ternary system was constructed at a temperature 1070 K based on the results of X-ray phase, microstructural analyzes and energy-dispersive X-ray spectroscopy in the whole concentration range. At the temperature of investigation, two new ternary compounds are realized in the system: TmCr6Ge6 (SmMn6Sn6 structure type, space group P6/mmm, a=0.51506(1), c=0.82645(2) nm) and Tm4Cr4Ge7 (Zr4Co4Ge7 structure type, space group I4/mmm, а=1.39005(9), с=0.54441(1) nm). Inclusion of Cr atoms in the structure of the binary germanide TmGe2 (structure type ZrSi2) up to 10 at. % Cr leads to the formation of a solid solution TmCrxGe2 (x = 0-0.33).